Astrophysics: A Very Short Introduction - Binney, Jams (New York Oxford University Press, 2016)
Astrophysics is said to have been born when Isaac Newton saw an apple drop in his orchard and had the electrifying insight that the Moon falls just like that apple. James Binney shows how the application of physical laws derived on Earth allows us to understand objects that exist on the far side of the Universe.
Includes Index and Illustrations.
Keywords: Astrophysics